2016
DOI: 10.1002/pmic.201500267
|View full text |Cite
|
Sign up to set email alerts
|

Multiclassifier combinatorial proteomics of organelle shadows at the example of mitochondria in chromatin data

Abstract: Subcellular localization is an important aspect of protein function, but the protein composition of many intracellular compartments is poorly characterized. For example, many nuclear bodies are challenging to isolate biochemically and thus remain inaccessible to proteomics. Here, we explore covariation in proteomics data as an alternative route to subcellular proteomes. Rather than targeting a structure of interest biochemically, we target it by machine learning. This becomes possible by taking data obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…This led to the observation that function at a subcellular location can also be inferred from proteomics data alone. This follows a two-step procedure: first, proteins are quantified across multiple biochemical isolations of a cellular structure, obtained from differently perturbed cells as starting material 3, 8. Second, one determines the covariation of all identified proteins with known functional components of that organelle (Figure 1).…”
Section: A Potential Solution: Adding Function To Localizationmentioning
confidence: 99%
See 2 more Smart Citations
“…This led to the observation that function at a subcellular location can also be inferred from proteomics data alone. This follows a two-step procedure: first, proteins are quantified across multiple biochemical isolations of a cellular structure, obtained from differently perturbed cells as starting material 3, 8. Second, one determines the covariation of all identified proteins with known functional components of that organelle (Figure 1).…”
Section: A Potential Solution: Adding Function To Localizationmentioning
confidence: 99%
“…The ‘behavior similarity’ or covariation can be measured using multi-classifier combinatorial proteomics (MCCP) [1], which is based on another machine-learning approach, random forests. So far, both chromatin components 1, 3 and mitochondrial proteins [8] can be determined on the basis of their covariation, suggesting this could be a general method to determine functional organelle composition and an alternative to approaches based on co-fractionation. Indeed, covariation was better suited to distinguish functional from non-relevant chromatin-bound proteins than classical, purification-based approaches [3].…”
Section: A Potential Solution: Adding Function To Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is known that different tissues show different levels of respiratory activity and variable amounts of mitochondria (Kirby et al , 2007; Fernández‐Vizarra et al , 2011) and that the number and composition of organelles can be affected, for example, by the aging process (Cellerino & Ori, 2017). Covariation of protein abundance across different conditions can be also exploited, and it can contribute to functional proteomics (Kustatscher et al , 2016). Currently, there is a lack of systematic approaches able to detect and deal with differences in cellular organization that might influence the outcome of proteomics data analysis from unfractionated samples.…”
Section: Introductionmentioning
confidence: 99%
“…Proof-of-principle studies by us and others have shown that protein covariation can be used to infer, for example, the composition of protein complexes and organelles [34][35][36][37][38][39][40][41][42] . However, these studies have focussed on relatively small sets of proteins or biological conditions, or used samples tailored to the analysis of specific cellular structures.…”
mentioning
confidence: 99%